KONFLIK TOKOH LENA DALAM CERITA â€œDREI TAGE LIEBEâ€ KARYA JOE LEDERER - SETIANINGRUM, AYU (IDENTITAET, 2016)
Lena’s conflict in Drei Tage Liebe choosen as a research object because the story was popular, then in 1931 adapted become a film. The purpose of this research are (1) To find Lena’s conflict types in Drei Tage Liebe by Joe Lederer, and (2) to find causes of Lena’s conflicts in Drei Tage Liebe by Joe Lederer. There are two research problem in this thesis: (1) what types of conflict  experienced by Lena in Drei Tage Liebe by Joe Lederer? (2) what caused Lena’s conflict in Drei Tage Liebe by Joe Lederer?. This research method is descriptive qualitative. The data analyzed using conflict theory by Nurgiyantoro and suported by Gorys Keraf theory, as for analize causes of conflicts using Jalaludin Rahkmat theory. The result of this research are: (1) there are two types of Lena’s conflicts, internal and external. The internal conflict experienced by Lena is self conflict, otherwise external conflict is conflict with the other characters. (2) the causes of Lena’s conflict are influenced by these factors: (1) sociogenesis motive, (2) behaviour, (3) emotion, (4) conative component, and (5) cognitive component. Key words: Internal conflict, Eksternal conflict, Lena, Drei Tage Liebe